Modular antenna of photosystem I in secondary plastids of red algal origin: a Nannochloropsis oceanica case study - Bína, David; Gardian, Zdenko; Herbstová, Miroslava; Litvín, Radek (Photosynthesis research, 2017)
Photosystem I (PSI) is a multi-subunit integral pigment-protein complex that performs light-driven electron transfer from plastocyanin to ferredoxin in the thylakoid membrane of oxygenic photoautotrophs. In order to achieve the optimal photosynthetic performance under ambient irradiance, the absorption cross section of PSI is extended by means of peripheral antenna complexes. In eukaryotes, this role is played mostly by the pigment-protein complexes of the LHC family. The structure of the PSI-antenna supercomplexes has been relatively well understood in organisms harboring the primary plastid: red algae, green algae and plants. The secondary endosymbiotic algae, despite their major ecological importance, have so far received less attention. Here we report a detailed structural analysis of the antenna-PSI association in the stramenopile alga Nannochloropsis oceanica (Eustigmatophyceae). Several types of PSI-antenna assemblies are identified allowing for identification of antenna docking sites on the PSI core. Instances of departure of the stramenopile system from the red algal model of PSI-Lhcr structure are recorded, and evolutionary implications of these observations are discussed.
Keywords: plastidy; fotosystém I (proteinový komplex); Photosystem I Protein Complex; Rhodophyta; Plastids; Spectrophotometry, Ultraviolet; spektrofotometrie ultrafialová